2020
DOI: 10.14716/ijtech.v11i3.3983
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Air Bubbles-Cetyltrimethylammonium Bromide (CTAB) Surfactant for Recovering Microalgae Biomass in a Foam Flotation Column

Abstract: Owing to their efficient photosynthesis, microalgae tend to possess superior growth rates and high lipid production, hence their significance to the biofuel sector. The bulk harvesting of microalgae from cultures is a substantial stage in advancing the production of biomass-based fuels. However, a reliable and cost-effective harvesting technology is not yet available. Foam flotation, which is a subcategory of the adsorptive bubble separation process, shows considerable promise for the harvesting and enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Kinetic model assessment exhibited that the discrete rate constant (i.e., modified Kelsall kinetic model) well-suited the trial data, where it showed the highest values of adjusted R 2 (>0.995). 75 Tributyl tetradecyl-phosphonium chloride (TTPC), a novel cationic surfactant for the separation of quartz from magnetite using cationic reverse flotation, was investigated in the study. From the thickness functional zeta potential, theory calculations, and measurement of an adsorption isotherm it is anticipated that TTPC may be a favorable type of collector, also, more preferable compared to dodecyl triethylammonium chloride.…”
Section: Environmental Science: Water Research and Technology Critica...mentioning
confidence: 99%
“…Kinetic model assessment exhibited that the discrete rate constant (i.e., modified Kelsall kinetic model) well-suited the trial data, where it showed the highest values of adjusted R 2 (>0.995). 75 Tributyl tetradecyl-phosphonium chloride (TTPC), a novel cationic surfactant for the separation of quartz from magnetite using cationic reverse flotation, was investigated in the study. From the thickness functional zeta potential, theory calculations, and measurement of an adsorption isotherm it is anticipated that TTPC may be a favorable type of collector, also, more preferable compared to dodecyl triethylammonium chloride.…”
Section: Environmental Science: Water Research and Technology Critica...mentioning
confidence: 99%
“…However, this process is categorized as complex. This process's complexity will be significantly influenced by several factors, such as solution pH, temperature, biosorbent dosage, ionic strength, initial solute concentrate, agitation rate, time, nutrients, light intensity, and salinity (Shihab, Dhahir, and Mohammed, 2020;Luangpipat and Chisti, 2017;Lee, Jalalizadeh, and Zhang, 2015;Das, 2010). These process parameters can either support or conflict with the performance of the biosorption process.…”
Section: Introductionmentioning
confidence: 99%
“…One of the alternative renewable energy resources that can meet global demand is biomass in the form of third-generation biofuels (Alaswad et al, 2015). The third generation of biofuels, especially those derived from microalgae biomass, is an ideal source of raw materials and has advantages over the first and second generations biofuels in terms of cultivation, lipid composition, product yield, viscosity, density, and calorific value of biofuels (Mahfud et al, 2020;Shihab et al, 2020). However, the conversion efficiency of biofuel production from microalgae compared with biofuels from other biomass is still very low (Rizzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%